Primed abortive initiation of RNA synthesis by E. coli RNA polymerase on T7 DNA. Steady state kinetic studies. - Smagowicz, W J (1978)
Ternary complexes of T7 DNA, RNA polymerase and the antibiotic rifampicin carry out the promoter specific abortive initiation when dinucleoside monophosphates were employed as primers. Primed abortive initiation, leading to synthesis of trinucleoside diphosphates, only occured with combinations of primers and substrates complementary to a promoter region of 8 base pairs centered around the origin of transcription. The steady state kinetics of three abortive initiations at T7 promoter A3 were studied in detail. The reactions appeared to be truly ordered. Affinity constants, maximal velocities and elementary step rate constants were thus obtained. The stimulation by dinucleoside monophosphate primers is brought about by positively effecting the function of the substrate site rather then by their higher affinity to the primer site of the transcriptional complex.